Remdesivir in COVID-19: A Retrospective Analysis of Remdesivir Effectiveness and the Relation with Blood Type Variation - Elsa Vera Denida Purba; Retnosari Andrajati; Nadia Farhanah Syafhan; Aditya Wirawan (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
identify the profile of the effectiveness of Remdesivir (RDV) therapy and its relationship to blood type variations in COVID-19 patients at Universitas Indonesia Hospital (RSUI).Methods: Variations in blood types were examined for their influence on the effectiveness in Covid-19 infected patients with RDV as an antiviral treatment. Data for this study were acquired at RSUI using a retrospective cross-sectional method. The sample is infected patients with COVID-19 from January 2021 to December 2021 who received RDV therapy. The parameters of the effectiveness of the treatment was a reduction of minimally 2 points on the WHO Clinical Progression Scale after 14 days of Remdesivir administration.Results: RDV effectiveness percentage shows 57.5% of patients experienced clinical improvement. The analysis results of the effect of blood type variations on clinical outcomes significantly affect the effectiveness of RDV therapy (OR: 1.705, 95% CI: 1.091–2.665; p = 0.019) but insignificant in terms of mortality status (OR: 0.654, 95% CI: 0.383–1.117; p = 0.120).Conclusion: Blood type variations significantly affected the effectiveness of RDV therapy in infected COVID-19 patients.